Symptom Burden and Health-Related Quality of Life Among Patients with Heart Failure in Indonesia - Masroni, Masroni; Chen, Hsing-Mei (International Journal of Psychosocial Rehabilitation, 2020)
Heart Failure (HF) is a complex syndrome that can cause a variety of symptoms, leading to a greater symptom burden than other chronic diseases, and contribute to poor health-related quality of life (HRQOL). This study aimed to examine the relationship between symptom burden and HRQOL among patients with HF in Indonesia. This study used a cross-sectional research design. A convenience sample of 164 heart failure patients was recruited from the cardiology department at a public hospital in Indonesia. A set of questionnaires was used including the Memorial Symptom Assessment Scale-Heart Failure (MSAS-HF) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and hierarchical regression analysis was utilized to analyze the data. All participants experienced a mean of 9.72 ± 5.44 symptoms, in which chest pain and lack of energy were the most prevalent, while chest pain, lack of energy, dif iculty sleeping, numbness/tingling in hands/feet and cough were the most burdensome symptoms. After controlling for demographic factors and illness-related factors, hierarchical multiple regression analysis showed that higher NYHA classes, psychological symptoms and heart failure symptoms predicted 55.1% of the variance in HRQOL. The study found that patients who experienced poor HRQOL also had greater symptoms burden. Future interventions should be directed to ameliorate symptom burden in order to improve HRQOL.